ANALYSIS OF SOCIAL MEDIA MARKETING ON REPURCHASE INTENTION - Wardhani, Natasha Kusuma (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The purpose of this study is to determine the effect of social media marketing on repurchase intention. Method: The method used is a literature review of references from online journals and foundations. Results: The results of this study indicate that social media marketing can have a clear positive and significant impact if there are additional mediating variables. These variables can be brand trust, brand image, and customer satisfaction. If only social media marketing is expected to influence repurchase intention, the results are still positive but not significant. Novelty: This study highlights the importance of mediating variables in strengthening the relationship between social media marketing and repurchase intention, emphasizing that social media marketing alone may not yield significant results without these additional factors.